A Field Study on the Indoor Thermal Environment of the Airport Terminal in Tibet Plateau in Winter. (2nd April 2017) - Zhen, Jianglong; Lu, Jun; Huang, Guangqin; Zeng, Liyue; Lin, Jianping; Xia, Hongtao
Abstract : In order to study the characteristics of indoor thermal environment in the airport terminal in Tibet Plateau with radiant floor heating in winter, a field measurement of the indoor thermal environment was conducted in Lhasa Gonggar Airport terminal 2. First, the unique climate characteristics in Tibet Plateau were analyzed through comparison of meteorological parameters in Beijing and Lahsa. The thermal environment in the terminal was divided into outer zone and inner zone as well as south zone and north zone. Thermal environment parameters including air temperature, black globe temperature, relative humidity in each zone, and inner surface temperature of envelope were measured and analyzed. Meanwhile, temperature and relative humidity in the vertical direction were measured. In addition, PMV and PPD were calculated for evaluating the thermal environment in the terminal. The findings can provide guidance for the design and regulation of thermal environment in terminals in Tibet Plateau in China.